Etiological and epidemiological factors of olive tree tuberculosis - Romero Raya, Pedro (Ars Pharmaceutica (Internet), 1967)
In this work we describe the isolating of 90 strains of Pseudomonas savastanoi from tumors of olive trees suffering, from tuberculosis. They have been submited to 34 different biochemical tests choosing those more suitable for their rapid and sure identification. Their antibiotic sensitivity has been carried out "Kanamicine" being the most active agent against bacteria "in vitro". The stem of Phaseolus vulgaris is a very good place to demonstrate the degree of virulence of Ps. savastanoi in the laboratory. The bacteriological and serological characteristics of the strains isolated are also described.